Q-switched Ytterbium doped fibre laser using gold nanoparticles saturable absorber fabricated by electron beam deposition - Ahmad, Muhammad Taufiq; Muhammad, Ahmad Razif; Haris, Hazlihan; Rahim, Hazli Rafis Abdul; Zakaria, Rozalina; Ahmad, Harith; Harun, Sulaiman Wadi (Elsevier, 2019)
A stable Q-switched Ytterbium doped fibre laser (YDFL) is demonstrated based on ring cavity by incorporating gold nanoparticles (AuNPs) based saturable absorber (SA). The SA is fabricated by depositing AuNPs onto polyvinyl alcohol thin-film surface using electron beam deposition technique. The proposed laser generates Q-switching pulses train as the pump power is increased beyond 61.1 mW. The laser operates at 1063.5 nm with the maximum repetition rate of 61.88 kHz and the thinnest pulse width of 4.23 μs are recorded at the 87.3 mW pump power. The output power increases linearly up to 3.14 mW, while the pulse energy varies from 10.55 nJ to 50.74 nJ as a pump power increased. Meanwhile, the maximum peak power of 12 mW is obtained at the pump power of 87.3 mW. © 2019 Elsevier GmbH